Computational de-orphanization of the olive oil biophenol oleacein: Discovery of new metabolic and epigenetic targets. (September 2019) - Cuyàs, Elisabet; Castillo, David; Llorach-Parés, Laura; Lozano-Sánchez, Jesús; Verdura, Sara; Nonell-Canals, Alfons; Brunet, Joan; Bosch-Barrera, Joaquim; Joven, Jorge; Valdés, Rafael; Sanchez-Martinez, Melchor; Segura-Carretero, Antonio; et al.
Abstract: The health promoting effects of extra virgin olive oil (EVOO) relate to its unique repertoire of phenolic compounds. Here, we used a chemoinformatics approach to computationally identify endogenous ligands and assign putative biomolecular targets to oleacein, one of the most abundant secoiridoids in EVOO. Using a structure-based virtual profiling software tool and reference databases containing more than 9000 binding sites protein cavities, we identified 996 putative oleacein targets involving more than 700 proteins. We subsequently identified the high-level functions of oleacein in terms of biomolecular interactions, signaling pathways, and protein-protein interaction (PPI) networks. Delineation of the oleacein target landscape revealed that the most significant modules affected by oleacein were associated with metabolic processes (e.g., glucose and lipid metabolism) and chromatin-modifying enzymatic activities (i.e., histone post-translational modifications). We experimentally confirmed that, in a low-micromolar physiological range (<20 μmol/l), oleacein was capable of inhibiting the catalytic activities of predicted metabolic and epigenetic targets including nicotinamide N-methyltransferase, ATP-citrate lyase, lysine-specific demethylase 6A, and N-methyltransferase 4. Our computational de-orphanization of oleacein provides new mechanisms through which EVOO biophenols might operate as chemical prototypes capable of modulating the biologic machinery of healthy aging. Graphical abstract: Image 1 Highlights: The chemical environment of the phenolic fraction of extra virgin olive oil (EVOO) remains essentially uncharted. Computational de-orphanization of the EVOO biophenol oleacein identified ∼1000 putative targets involving 700 proteins. The oleacein target landscape notably involves metabolic processes and chromatin-modifying enzymatic activities. Oleacein inhibits the catalytic activities of NNMT, ACLY, KDM6A/UTX, and DOT1L at physiological concentrations.